German Public Finances through the Financial Crisis1. (December 2015) - Blömer, Maximilian J.; Dolls, Mathias; Fuest, Clemens; Löffler, Max; Peichl, Andreas
Abstract: The German experience of the financial crisis was very different from that of most other European countries. Germany was hit by a very strong shock that was relatively concentrated in the exporting, manufacturing industries. In addition, the German labour market was very resilient during the crisis due to earlier labour market reforms and policy instruments facilitating labour hoarding. As a consequence, the public finances were only moderately affected and not many policy reforms had to be enacted. This paper presents the German experience of the financial crisis. We start by presenting the macroeconomic situation and how the crisis unfolded in Germany, before focusing on the situation of the public finances. Finally, we analyse the policy responses to the financial crisis.